Geospatial Analysis for Detection of Sinkhole Distribution and Change in Kinta Valley, Malaysia - Suleiman Alkouri, Omar Mahmoud (2009)
The geospatial study of Karst over 25 years uncontrolled use and the resulting environmental impact in Kinta Valley area-Malaysia is described. The geo-hazard map for sinkholes distribution was developed and the changes of limestone topography were analyzed as well as the relative importance of geological and geo-morphological factors. Due to intensification of human activities the Karst has suffered several environmentally relevant changes. An assessment of the degree of hazard was conducted by utilizing 10 m2 cell dimension. The results showed that the land use in terms of urbanization and industrialization has a direct influence on the Karst features development. The geohazard map indicated that 93 % of sinkholes occurrence were located in the high and very high potential hazard areas in contrast to the areas in the middle and southwest of the Kinta valley. The highest sinkhole occurrence was recorded in January 2005 which was attributed to the earthquake on 26th December, 2004. The sinkhole formation was further aggravated by heavy rainfall and surface mining. Fortunately, our spatial temporal data model facilitated the delineation of the changes in Karst topography. A geo-statistical investigation was carried out on the nature of topographic variation and its roughness to ascertain the nature of Karst and its distinctiveness from non-Karst landscapes. Bukit Merah village was preferentially selected for a case study. The condition of the mining site from 1991 to 2007 was revealed by False color composites of land-observing satellites the Thematic Mapper and Satellite Pour l'Observation de la Terre, the mining activities at the site increased by 383 % over the study period. The area of the water body increased progressively from 0.972 km2 in 1991 to 3.726 km2 in 2007. Given the current degradation scenario of the limestone resources in Kinta Valley and associated environmental impacts, the study emphasizes the need for conservation of these valuable resources.